Ivey Executive Development. Issue 2 (5th May 2016) - Anderson, Joe; Williams, Susan K.
Abstract : Synopsis: The Ivey Business School recently decided to outsource its printing to ProPrintR. Barbara Pokropek, Ivey Executive Development (IED), was faced with managing IED's outsourced printing jobs. There had been an increasing number of quality issues with the binder that ProPrintR prepared for IED's executive classes. While binder material errors may not sound like a big deal, for IED these materials are part of their branding and can lead to executive student dissatisfaction. This case describes the evolution of the current situation and challenges students to consider how to manage the situation. Research methodology: The situation described in this critical incident is real, only the name of the print provider has been changed. Barbara Pokropek was interviewed and she provided the data and examples described. Ms Pokropek reviewed and provided input to revise the manuscript. Relevant courses and levels: This case is intended for undergraduate core operations management classes. It can be used to discuss supplier relations and supply management. As such there are multiple dimensions to the case: importance of clearly delineating the work needed, defining performance expectations and metrics for a supplier, selecting quality tools to help measure performance, and centralized vs decentralized supply management.